Families changing families: The protective function of multi-family therapy for children in education. (October 2014) - Morris, Emma; Le Huray, Corin; Skagerberg, Elin; Gomes, Rosemary; Ninteman, Aafke
The Marlborough Family Education Centre (MFEC) uses a specific multi-family group approach with families where children exhibit (primarily) conduct problems and function poorly in school. Research indicates that failure to intervene with these children carries great potential cost to both the family and society. Outcomes for 50 families receiving intervention from the MFEC were compared with a control group of 28 who had access to a range of interventions, but not the multi-family group approach pioneered by the MFEC. Data on child and family social, emotional and behavioural functioning were collected at the point of referral, and at 6 and 12 months. Parents of children receiving support from the MFEC reported statistically and clinically significant improvements in their children that were maintained at 12 months whereas there was no change in the control group. In addition, measures of family functioning were fairly stable for the MFEC group, while the control group showed significant deterioration over the same time period. Other results were not significant. These findings are interpreted within the context of early intervention. The methodological limitations of the study are considered and suggestions for future research are outlined.